Problematika Pembelajaran Online pada Aspek Perkembangan Bahasa Anak Usia Dini di Masa Pandemi Covid-19 dan Merdeka Belajar - Anggraini, Kristin; Prastyo, Danang (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
This article describes the impact of online learning carried out during the Covid-19 pandemic and its role in aspects of early childhood language development that occurred in the era of independent learning. The factors that cause the underdevelopment of aspects of early childhood language development include the low ability of children to speak, the lack of opportunities for communication between teachers and children during the implementation of online learning resulting in children often being silent when participating in face-to-face learning conducted in the era of independent learning In this case, the child becomes less cheerful and less confident. This happens because during online learning, children are used to being assisted and accompanied by their parents, which makes children dependent on always being assisted by their parents when completing assignments, and makes children feel a little uncomfortable meeting the teacher when carrying out face-to-face learning in the era of independent learning, such as at the moment. So that efforts are needed from teachers to be able to improve aspects of early childhood language development by primarily paying attention to children's needs, especially in the era of independent learning. The research method in this research uses literature study, where researchers will record and analyze various sources, including journals, books, and various forms of documents related to the impact of online learning on aspects of early childhood language development. As for the results, teachers must be able to adapt to the use of information technology in order to create interesting and fun learning and be able to develop aspects of children's language development through face-to-face and online learning activities in the era of independent learning.